2014
DOI: 10.15376/biores.9.3.4266-4273
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobically Modified Celluloses as Novel Cholesterol-lowering Polymers

Abstract: Hydrophobically modified celluloses were prepared by the esterification of monocarboxycellulose (MCC) and carboxymethylcellulose (CMC) with methanol, followed by the amino-de-alkoxylation of the methyl esters with n-octadecylamine. These cellulose derivatives were fed at 30 and 60 g/kg for 4 weeks to female rats. The diets were supplemented with palm fat (60 or 50 g/kg) and cholesterol (0 or 10 g/kg). There was no significant effect of amidated celluloses on the feed intake or body weight of rats. Both MCC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The total hepatic and faecal lipids were extracted with 2:1 chloroform-methanol and measured gravimetrically [14]. Hepatic cholesterol was saponified with 2M ethanolic KOH (1 h at 100 °C), extracted with ethyl ether, derivatised using trimethylchlorosilane and hexamethyldisilazane (Sigma-Aldrich, Prague, Czech Republic), and determined using gas chromatograph equipped with SAC- 5 (Supelco, Bellefonte, USA). The 5α-cholestane at 0.5 mg/ml was used as the internal standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total hepatic and faecal lipids were extracted with 2:1 chloroform-methanol and measured gravimetrically [14]. Hepatic cholesterol was saponified with 2M ethanolic KOH (1 h at 100 °C), extracted with ethyl ether, derivatised using trimethylchlorosilane and hexamethyldisilazane (Sigma-Aldrich, Prague, Czech Republic), and determined using gas chromatograph equipped with SAC- 5 (Supelco, Bellefonte, USA). The 5α-cholestane at 0.5 mg/ml was used as the internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…The latter hypocholesterolemic agents are anion-exchange resins which bind bile acids and increase their faecal excretion [2], and ezetimibe, a cholesterol absorption inhibitor that targets uptake at the jejunal enterocyte brush border [3]. An alternative to bile acid sequestrants are hydrophobic sorbents of neutral sterols: amidated pectin [4], amidated celluloses [5,6], and amidated alginate [7,8]. Amidated alginate is an effective cholesterol-lowering agent and sorbent of dietary fat.…”
mentioning
confidence: 99%
“…Experiments on rats showed that amidated pectin and amidated cellulose are efficient hypocholesterolemic agents (Marounek et al 2013;Tůma et al 2014). In an unpublished pilot-scale experiment by the authors, however, the hypocholesterolemic effects of amidated carboxymethylcellulose and amidated monocarboxycellulose were not consistent with low fecal excretion of sterols.…”
Section: Introductionmentioning
confidence: 91%
“…The total hepatic and fecal lipids, fecal neutral sterols, and bile acids were determined as described previously (Tůma et al 2014). Conjugated bile acids in the feces were extracted with methanol for 30 min at 60 °C, applied to a Strata C18-E column (Phenomenex, Torrance, CA, USA), washed with water and acetone, and eluted with methanol (Roda et al 1992).…”
Section: Analysesmentioning
confidence: 99%
“…The serum levels of total cholesterol, LDL-cholesterol, triacylglycerols, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) were determined using commercial kits (Erba-Lachema, Ltd., Brno, Czech Rep.). The total hepatic and faecal lipids, faecal neutral sterols and bile acids were determined as described previously [13].…”
Section: Composition Of Control and Experimental Diets G/kgmentioning
confidence: 99%